Additional income applications based on job performance criteria at Pt. Bank Sinarmas Tbk (Kcp) Tebing Tinggi Jambi - Arisman; Nurmina Siregar (Journal of Applied Accounting And Business, 2019)
PT Bank Sinarmas Tebing Tinggi Jambi is an element of the company in the field banking. Supplemental income is income derived based on the outcome of a month's performance achievement beyond the legally-accepted wage. In processing and additional income on PT Bank Sinarmas Tebing Tinggi Jambi still Microsoft Excel 2007 so that the results are less rapid, precise and accurate and frequent detection of data redundancy (double). One way to overcome this problem is to create an information system that uses Microsoft Visual Basic 2008 programming language as well database Microsoft Access 2007 as the database. Which, in making this information system we use system design methods such as. UML stands for Unified Modeling Language, the tool used is Use Case, Activity, and Class diagram.. This research aims to have this information system Supplemental income PT Bank Sinarmas Tebing Tinggi Jambi is an element of the implementation of municipal governments precise and accurate and no redundancies